KIDNEY STONE DISEASE: CHRONIC PROSTRATION, MODERN CHECK METHODS AND TREATMENT (World Bulletin of Public Health, 2025)
In the article kidney stone disease causes, risk factors, diagnostics methods and modern treatment measures are illuminated. Kidney stones urine on the roads harvest are mineral structures that occur and they pain, urine release difficulty and other health problems brought release possible. Chronic prostration kidney of activity decreases as a result of the surface comes and general fatigue syndrome as manifestation will be. Modern medicine kidney stones diagnosis and treatment for various treatment methods, including ultrasound controller, computer tomography, lithotripsy and surgery practices. In the article, the disease prevention to take according to recommendations are also provided.
Keywords: Kidney stone disease; nephrolithiasis; chronic prostration